AN ANALYSIS OF GRAMMATICAL ERRORS IN STUDENTS’ WRITING DESCRIPTIVE TEXT - Seli Royani; Sari Sadiah (PROJECT (Professional Journal of English Education), 2019)
Writing is considered as the most complicated skill to be mastered required not only great vocabularies but also grammar, as Harmer (2004:31) cited in (Wati & Nursyaebah, 2017) states that, when writing, learners often have more time to think than they do in spoken activities. Therefore, they can stimulate their brain,even consult dictionaries, grammar books or other reference material to help them . He believes that grammar is really important in writing that is why he suggested to consult grammar books to make the writing grammatically correct. Therefore, the basic objective of this study is to analyze students’ grammatical errors in writing especially in descriptive text. In addition, (Wati & Nursyaebah, 2017) there are six classifications of grammatical error; those are verb agreement (Leech, 1985), capitalization (Oshima, 1988) usage, sentence pattern (Ross, 1975) pronoun and spelling (Brooks, 1964). The data were analyzed based on the error analysis’s of students in writing. In the research finding it showed that students mostly did error in verb agreement 41% that caused by using incorrect fromsimple present, followed by pronoun 18%, usage 15%, sentence pattern12%, spelling 9%, and capitalization error 5%. From the result finding, it is necessary or students learn more about English grammar and it is suggested for teacher to re-teaching about verb agreement and pronoun as the most failure which students mostly did in their writing.